Lanthanum hexaboride coated D-shaped fibre for Q-switched pulse generation. Issue 17 (7th October 2022) - Omar, S.; Musa, B.; Ahmed, N.; Jusoh, Z.; Rahman, H. A.; Rosol, A. H. A.; Apsari, R.; Harun, S.W.
Abstract : A lanthanum hexaboride (LaB6 )-coated D-shape fibre was successfully employed in an erbium-doped fibre laser cavity as a saturable absorber (SA) for pulse generation via the Q-switching mechanism. The Q-switched laser was obtained with an operation wavelength of 1561.4 nm within a pump power range between 82.0 and 97.6 mW. The maximum pulse rate of 57.41 kHz, minimum pulse duration of 4.49 µs and maximum pulse energy of 73.94 nJ were obtained at a 97.6 mW pump. Our results indicate that LaB6 is a promising SA material used for generating a stable and low-cost pulsed laser.